Demokrasi Semu: Politik Pencitraan dalam Bingkai Islam dan Implikasi Terhadap Good Governance - Fithriyyah, Mustiqowati Ummul; Astuti, Atika Windi; Umam, Muhammad Saiful; Wahyu Ningsih, Risma Lutfia (State Islamic Institute of Kudus (IAIN Kudus), 2021)
PSEUDO DEMOCRACY: POLITICAL IMAGING WITHIN ISLAMIC FRAMEWORK AND IMPLICATIONS FOR GOOD GOVERNANCEIndonesia, as a Muslim-majority country, weaponizes Islam in politics to win over the voices of Muslims in the country. This method is not allowed to be implemented in Indonesia which adheres to a democratic system. Principally, political imaging is carried out in order to influence society by instilling opinions. Regardless of the purpose of imaging, gaining public trust is way more important rather than just having a good image. Public trust is gained through the credibility of the candidates. The said credibility is achieved when the candidates act in a way that is in line with what they said or promised. Candidates can apply political imagery through good governance to gain public trust without having to accentuate the image of the politicization of Islam. This article aims to see how political imaging should be carried out from an Islamic perspective. The method used to study the problems is qualitative. The result of this study shows that the plurality that exists in Indonesia requires special attention from the government to manage the political religions which can create controversy between religious communities. In order to build an essential democracy in Indonesia and avoid the presence of political power of religious identity in the political arena, every candidate must avoid identity involvement in the electoral arena as a way of avoiding the awakening of identity and its sentiment that occurs in Indonesia.